Galur Harapan Padi Sawah Dataran Tinggi Berumur Genjah - Syahrul Zen (Jurnal Penelitian Pertanian Terapan, 2013)
Evaluation the lines of rice the highlands of aims to identify lines being sappy the result of higher than varieties Sarinah and Inpari 28 Kerinci. As many as 24 lines rice early maturity together varieties Sarinah and Inpari 28 Kerinci by contrast has been tested power results in Kayu Aro Solok West Sumatra ( 850 m above sea level). Research using randomized block design with three replications. m Fertilizer aplicated at rate of 200 kg of Urea, 100 kg SP 36 and Kcl 100 kg/ha. The 25 days old seedling after sowing were planted in 3x4 m2 size plots with plant spacing 25 x 25 cm and three seedling per hole. The research results obtained seven lines of lawland rice fields into alleged able to adapt to increased production in cumulative range 0.31-0.82 t/ha compared to varieties Sarinah, the seventh such lines is BP13990-3B-GRT-3-1-7-2, BP13990-3B-GRT-3-1-7-8, BP13990-3B-GRT-3-1-7-9, BP13990-3B-GRT-3-1-8.4, BP13990-3B-GRT-3-1-7-4, BP13990-3B-GRT-3-1-8-8 and BP14022-10B-GRT-2-3-2. Age of plant lines are more early than varieties Sarinah and Inpari 28 Kerinci. The power steadiness and power adaptation results of lines that needs to be evaluated on a different environment conditions. Keywords : advanced yield trial, lines rice, high elevation